2022
DOI: 10.3389/fimmu.2022.939768
|View full text |Cite
|
Sign up to set email alerts
|

Viral Circular RNAs and Their Possible Roles in Virus-Host Interaction

Abstract: Circular RNAs (circRNAs) as novel regulatory molecules have been recognized in diverse species, including viruses. The virus-derived circRNAs play various roles in the host biological process and the life cycle of the viruses. This review summarized the circRNAs from the DNA and RNA viruses and discussed the biogenesis of viral and host circRNAs, the potential roles of viral circRNAs, and their future perspective. This review will elaborate on new insights gained on viruses encoded circRNAs during virus infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…Since then, multiple DNA and RNA viruses have been shown to encode viral circRNAs [ 109 , 110 , 111 , 112 ], and several reports have investigated the crucial role of virus-coded circRNAs in the intricate virus–host interaction. Nonetheless, the precise biological roles of virus-coded circRNAs are still elusive [ 113 , 114 ].…”
Section: Involvement Of Circrnas In Innate Immunity Against Viral Inf...mentioning
confidence: 99%
“…Since then, multiple DNA and RNA viruses have been shown to encode viral circRNAs [ 109 , 110 , 111 , 112 ], and several reports have investigated the crucial role of virus-coded circRNAs in the intricate virus–host interaction. Nonetheless, the precise biological roles of virus-coded circRNAs are still elusive [ 113 , 114 ].…”
Section: Involvement Of Circrnas In Innate Immunity Against Viral Inf...mentioning
confidence: 99%
“…Some recent studies have confirmed that circRNAs are encoded by RNA viruses such as the B. mori cytoplasmic polyhedrosis virus (BmCPV) [ 122 , 123 ]. The viral circRNAs have a number of biological roles, including controlling viral over-proliferation and preventing innate immunity from being activated [ 124 ]. In this section, we highlight the effect of circRNAs that are encoded by pathogens on the immune systems of insects.…”
Section: Pathogen-encoded Circrnas Hijack the Host System For Prolife...mentioning
confidence: 99%
“…Several viruses can alter the circRNA landscape of infected cells to modulate host gene expression ( Xie et al, 2021 ). Notably, viruses have been shown to exploit the cellular machinery to generate viral circRNAs for their own profit, while hosts may also use these molecules to suppress viral replication ( Zhang X. et al, 2022 ). The circRNAs epitranscriptome has also been linked to viral infections.…”
Section: The Non-coding Rna Epitranscriptome Landscape During Viral I...mentioning
confidence: 99%